The transparency fix : secrets, leaks, and uncontrollable government information - Fenster, Mark (Stanford, California : Stanford Law Books, an imprint of Stanford University Press, 2017)
Is the government too secret or not secret enough? Why is there simultaneously too much government secrecy and a seemingly endless procession of government leaks? The Transparency Fix asserts that we incorrectly assume that government information can be controlled. The same impulse that drives transparency movements also drives secrecy advocates. They all hold the mistaken belief that government information can either be released or kept secure on command. The Transparency Fix argues for a reformation in our assumptions about secrecy and transparency. The world did not end because Julian Assange, WikiLeaks, and Edward Snowden released classified information. But nor was there a significant political change. "Transparency" has become a buzzword, while secrecy is anathema. Using a variety of real-life examples to examine how government information actually flows, Mark Fenster describes how the legal regime's tenuous control over state information belies both the promise and peril of transparency. He challenges us to confront the implausibility of controlling government information and shows us how the contemporary obsession surrounding transparency and secrecy cannot radically change a state that is defined by so much more than information.
Introduction : the transparent state we want but can't have -- Liberating the family jewels : "free" information and "open" government in the post-war legal imaginary -- Supplementing the transparency fix : innovations in the wake of law's inadequacies -- Transparency's limits : balancing the open and secret state -- The uncontrollable state -- The impossible archive of government information -- Disclosure's effects? -- The implausibility of information control -- The disappointments of megaleaks -- Conclusion : the West Wing, the West Wing, and abandoning the informational fix.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 25, 2017).
eBooks on EBSCOhost
Keywords: Transparency (Ethics) in government -- Law and legislation -- United States; Freedom of information -- United States; Official secrets -- United States; Government information -- Law and legislation -- United States; Leaks (Disclosure of information) -- United States; Liberté d'information -- États-Unis.; Secrets d'État -- États-Unis.; Fuites (Divulgation d'informations) -- États-Unis.; POLITICAL SCIENCE -- Public Affairs & Administration; Freedom of information; Government information -- Law and legislation; Leaks (Disclosure of information); Official secrets; Transparency in government -- Law and legislation; United States; Internet resources